Evaluation of vaccination coverage of measles-rubella campaign in Imphal East District, Manipur: A cross-sectional study - Bishwalata Rajkumari; Avinash Keisam; Danny Singh Haobam; Tamphasana Thounaojam (Wolters Kluwer Medknow Publications, 2020)
Background: In India, the measles-rubella (MR) vaccination campaign was conducted with the purpose of vaccinating all children of 9 months-15 years of age with a single dose of MR vaccine. However, it encountered various challenges which may hamper with the coverage. Objectives: This study was conducted to evaluate the recently conducted MR campaign in Manipur pertaining to its coverage and factors for not vaccinating. Methods: The cross-sectional study was conducted in Imphal East district of Manipur during May and June 2018 among 1551 children from two communities. The study tool was adapted from the rapid convenience monitoring tool of the WHO. Descriptive statistics were generated, and multivariable logistic regression analysis was performed with vaccination status as dependent with selected independent variables. Results: Among the study children, 38% were in the age group of 5-10 years, males constituting 51.3%. Only two-third (68.8%) of the children had received the MR vaccine, coverage among Muslim children was 40.4% only, and 6.5% of the respondents reported some forms of adverse events following immunization. Children from the Meitei community were (odds ratio: 14.35, 95% confidence interval: 10.22-20.16) significantly more likely to receive the MR vaccination as compared to children belonging to the Muslim community (P = 0.001). Conclusion: Vaccination coverage of only 68.8% highlighted the need for increased sensitization and involvement of local and religious leaders in generating necessary awareness for improved coverage of the campaign.